Global stability of a three-species food-chain model with diffusion and nonlocal delays - Zhang, Xiao; Xu, Rui; Li, Zhe (Mathematical Modelling and Analysis, 2011)
In this paper, a three species reaction-diffusion food-chain system with nonlocal delays is investigated. Sufficient conditions are derived for the global stability of a positive steady state and boundary steady states of the system by using the energy function method. Numerical simulations are carried out to illustrate the theoretical results.